1983
DOI: 10.1002/pen.760231809
|View full text |Cite
|
Sign up to set email alerts
|

Ketocoumarins as photosensitizers and photoinitiators

Abstract: Several 3-ketocoumarins with alkoxy or dialkylaniino substituents in the 7 position, which are efficient sensitizers for crosslinkable polymers, were evaluated as photoinitiators. Proper combinations of certain derivatives of these ketocoumarins with activators such as amines, acetic acid derivatives, and alkoxypyridinium salts gave quantum yields for initiated radical polymerization much higher than that obtained from the Michler's ketonehenzophenone combinations. For each class of activators the dependence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 2 publications
0
29
0
Order By: Relevance
“…The same optical setup and the same solution are used in both in both measurements. Since the final state is excited by one-and two-photon absorption, in this case it can be assumed that the quantum efficiency t 1 and t2 are equal and the number densities nl and n2 are also equal [13,16]. Thus b for DEDC is determined as 29.5 x 10"50 cm4 s/photon.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same optical setup and the same solution are used in both in both measurements. Since the final state is excited by one-and two-photon absorption, in this case it can be assumed that the quantum efficiency t 1 and t2 are equal and the number densities nl and n2 are also equal [13,16]. Thus b for DEDC is determined as 29.5 x 10"50 cm4 s/photon.…”
Section: Resultsmentioning
confidence: 99%
“…The proper combinations of ketocoumarin dye with activators can gave high quantum yield for initiated radical polymerization. Williatns et al [13] reported that N-phemlglycine, in the presence of ketocoumarin dye, shows sensitivity in the visible region up to SSOmn. We used the ketocomnarin dye with titanocene compound photoinitiating system and obtained high initiating efficiency for visible light polymerization [14].…”
Section: Introductionmentioning
confidence: 99%
“…A wide spectrum of pharmacological activities was associated with coumarins such as antioxidant [3,4], antiinflammatory [5], anticoagulant [6], antibacterial [7], cytotoxic effects [8,9], anticancer [10], antiHIV [11,12] and dyslipidemic activities [13]. Coumarin derivatives also reported as vasorelaxant [14], free radical scavengers [15], triplet sensitizers [16] and lipid-lowering agents [17].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the coumarin derivatives are also reported as triplet sensitizers [2], anti-HIV agents [3], lipid-lowering agents [4], and antioxidants [5]. They also have been found to inhibit lipid peroxidation and to possess vasorelaxant [6], anti-inflammatory [7], anticancer [8], antibacterial, and antifungal activity [9,10].…”
Section: Introductionmentioning
confidence: 99%